Relación de las emisiones de gases de efecto invernadero con la temperatura en Ecuador - Mejía Vélez, Cristian Antonio (2022)
In order to identify the effects between greenhouse gas emissions, total CO2 emissions, CO2 >1000$, CO2 per capita, CH4, N2O, and other greenhouse gases such as CFCs, HFCs, PFCs and SF6 and the temperature in Ecuador during 40 years were determined. These were obtained from databases and the Pearson statistical model was applied, where an increase of 88% in total CO2 emissions and CO2 >1000$ was obtained, CO2 emissions per capita obtained 86%, in emissions CH4 emissions reached 85%, N2O emissions reached 83% and other GHG emissions reached 62%, demonstrating a strong linear relationship. Therefore, it is concluded that 82% of the behavior of the increase in temperature in Ecuador is attributed to GHG emissions, these being: anthropogenic activities are the main causes that exert forceful changes in the increase in temperature in Ecuador. Improvements were proposed in the National Greenhouse Gas Mitigation Plan of Ecuador that constituted the construction of the epistemological axis in sustainable development, environmental protection.